MANAGEMENT OF INFRASTRUCTURE FACILITIES IN IMPROVING THE QUALITY OF EDUCATION AT SD NAHDLATUL ULAMA, SLEMAN, YOGYAKARTA - Sari, Yunita; Ikhwan, Muh Saidil; Iffah, Rona Dhiya Layli (Jurnal Dedikasi Pendidikan, 2024)
The purpose of this study is to analyze the role of facilities and infrastructure in improving the quality of learning in elementary schools. Effective facilities and infrastructure are essential to create an effective learning environment and support student development. The study used observation, interviews, and documentation studies to collect data. Student motivation and learning outcomes improve in comfortable classrooms, ample learning opportunities, and a safe physical environment. The study also highlights the role of information and communication technology in improving the quality of education; High-speed internet access and adequate computing facilities allow students to access a wider and varied range of learning resources. This study will help to understand the importance of implementing facilities and infrastructure in improving the quality of elementary schools.